PERANCANGAN APLIKASI PEMESANAN MENU MAKANAN DAN MINUMAN BERBASIS ANDROID - Ade Hendini (Universitas Bina Sarana Informatika, 2013)
Android is a Linux-based operating system that is used to perform functions such mobile sms, phone calls, browsing, gaming and even other applications with a specific purpose and function is also available in android. One is to use android mobile food ordering in a restaurant or other eating places. Android mobile usage for ordering food can certainly help the business processes in a restaurant or eating place. Android mobile usage to record orders can replace paper and pen. Android mobile application users ordering food and beverages are the buyer (the waiter) which stores data ordering to MySql database server who is the part where the use of web-based PHP script that will see (receive) the data from the ordering customer, other than that part cashier as place-based payment desktop with java programming language also receive the data reservations on a table.Key words: Mobile android, MySQL, PHP, Java